Guidelines on the classification of diabetic foot ulcers (IWGDF 2019). (16th March 2020) - Monteiro‐Soares, Matilde; Russell, David; Boyko, Edward J.; Jeffcoate, William; Mills, Joseph L.; Morbach, Stephan; Game, Fran
Abstract: The International Working Group on the Diabetic Foot (IWGDF) has been publishing evidence‐based guidelines on the prevention and management of diabetic foot disease since 1999. This publication represents a new guideline addressing the use of classifications of diabetic foot ulcers in routine clinical practice and reviews those which have been published. We only consider systems of classification used for active diabetic foot ulcers and do not include those that might be used to define risk of future ulceration. The guidelines are based on a review of the available literature and on expert opinion leading to the identification of eight key factors judged to contribute most to clinical outcomes. Classifications are graded on the number of key factors included as well as on internal and external validation and the use for which a classification is intended. Key factors judged to contribute to the scoring of classifications are of three types: patient related (end‐stage renal failure), limb‐related (peripheral artery disease and loss of protective sensation), and ulcer‐related (area, depth, site, single, or multiple and infection). Particular systems considered for each of the following five clinical situations: (a) communication among health professionals, (b) predicting the outcome of an individual ulcer, (c) as an aid to clinical decision‐making for an individual case, (d) assessment of a wound, with/without infection, and peripheral artery disease (assessment of perfusion and potential benefit from revascularisation), and (d) audit of outcome in local, regional, or national populations. We recommend: (a) for communication among health professionals the use of the SINBAD system (that includes Site, Ischaemia, Neuropathy, Bacterial Infection and Depth); (b) no existing classification for predicting outcome of an individual ulcer; (c) the Infectious Diseases Society of America/IWGDF (IDSA/IWGDF) classification for assessment of infection; (d) the WIfI (Wound, Ischemia, and foot Infection) system for the assessment of perfusion and the likely benefit of revascularisation; and (e) the SINBAD classification for the audit of outcome of populations.